Peningkatan Life Skill dan Minat Wirausaha Siswa Melalui Bio-Entrepreneurship (BIOSHIP) SMK di Sawangan Depok - Aqil, Deden Ibnu; Hudaya, Adeng; H. Masri, Zainal Arifin (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
According to the Depok City BPS in 2017 the workforce (population aged 15-64 years) sawangan district totaled 115,038 people. While the working population amounted to 77,734 people (67.6%), the remaining 37,304 people (32.4%) did not work. The magnitude of the unemployment rate, which is 32.4%, is the highest unemployment rate, the youth whose education level is only up to the level of vocational high school and does not continue to college because of work orientation. The skills possessed and the interest in entrepreneurship for vocational school graduates in Sawangan sub-district is still very low. The community service activity that will be carried out aims to equip vocational students in Sawangan sub-district with entrepreneurial or entrepreneurial skills in this case with a bioenterpreneurship approach that is by making bio-based products that have economic value and have a selling value in order to prepare them for the next life if they later graduated from vocational high school. The problem of this activity is how the approach to applying biointerpreneurship learning to vocational students in Sawangan subdistrict is able to improve life skills and entrepreneurial interests. This activity is a learning that is oriented to bioentrepreneurship that is by involving elements of entrepreneurship in biological products.